Radical Feminism - Mackay, F. author. aut Link
IX, 324 p.
Keywords: Feminism is not dead. This groundbreaking book advances a radical and pioneering feminist manifesto for today's modern audience that exposes the real reasons as to why women are still oppressed and what feminist activism must do to counter it through a vibrant and original account of the global Reclaim the Night March.